Reception of social communication campaigns and effects of prevention messages among the population of Greater Tunis - Lamia Ben Hassine (International Journal of Social Communication, 2021)
A descriptive quota study was carried out among the population of Greater Tunis: "Knowledge, attitudes and acceptance of the messages on sexual and reproductive health (SRH)". Three hundred subjects participated in the survey most of them are female gender. The majority of the respondents did not benefit from awareness-raising sessions on SRH. Most respondents mentioned national radio and TV channels as the main source of information on SRH. This survey revealed that the level of reception of the actions carried out remains modest. Message communication actors should use diverse strategies that involve other larger interests of their receivers, when they have little enthusiasm for information. They can develop information by combining these themes with other themes that the receivers feel the need for.